Variations in the forest vegetation structure in rainy forests of the Manaus area (Central Amazon) - Costa, Gabriel; Crespi, Antonio Luis; Higuchi, Niro; Oliveira Fernandes, Cláudia; Martins, Álvaro; Castro, Adriano; Bernardos, Sonia; Amich, Francisco (Ecologia, 2006)
The moist forest vegetation in Central Amazon (North of Brazil) is developed on a very irregular relief, where five different toposequenties have been recognised: plateau, plateau/slope, slope, slope/lowland and lowland. The present work was focused on the characterization of the vegetation of two (20x2500 m2) perpendicular transects, oriented in the East-West and North-South directions, by means of a multivariate analysis. The methodology proposed may be considered as a useful analytical tool to evaluate the structure of the vegetation in the communities investigated here. The results obtained substantialy the existence of two major structural behaviour tendencies, affected by the extreme toposequencies, i.e., the plateau and the lowland. The discrimination between these two different tendencies is not very significant, thus confirming the limited influence of the altitude on the vegetation structure. Anyway, two opposite structural tendencies are registered, one of them for the most arid topossequence (plateau and plateau/slope) and the other for the most humid one (slope/lowland and lowland). These two tendencies are conected by continouos behaviour. The reason pointed out to explain this structural effect could be the important chaos induced by the β-diversity detected in this type of vegetation.
Variaciones en la estructura de la vegetación arbórea en bosques lluviosos de la región de Manaus (Amazonas Central)